Diverse mosquito-specific flaviviruses in the Bolivian Amazon basin. (8th March 2021) - Orba, Yasuko; Matsuno, Keita; Nakao, Ryo; Kryukov, Kirill; Saito, Yumi; Kawamori, Fumihiko; Loza Vega, Ariel; Watanabe, Tokiko; Maemura, Tadashi; Sasaki, Michihito; Hall, William W.; Hall, Roy A.; et al.
Abstract : The genus Flavivirus includes a range of mosquito-specific viruses in addition to well-known medically important arboviruses. Isolation and comprehensive genomic analyses of viruses in mosquitoes collected in Bolivia resulted in the identification of three novel flavivirus species. Psorophora flavivirus (PSFV) was isolated from Psorophora albigenu . The coding sequence of the PSFV polyprotein shares 60 % identity with that of the Aedes -associated lineage II insect-specific flavivirus (ISF), Marisma virus. Isolated PSFV replicates in both Aedes albopictus - and Aedes aegypti -derived cells, but not in mammalian Vero or BHK-21 cell lines. Two other flaviviruses, Ochlerotatus scapularis flavivirus (OSFV) and Mansonia flavivirus (MAFV), which were identified from Ochlerotatus scapularis and Mansonia titillans, respectively, group with the classical lineage I ISFs. The protein coding sequences of these viruses share only 60 and 40 % identity with the most closely related of known lineage I ISFs, including Xishuangbanna aedes flavivirus and Sabethes flavivirus, respectively. Phylogenetic analysis suggests that MAFV is clearly distinct from the groups of the current known Culicinae -associated lineage I ISFs. Interestingly, the predicted amino acid sequence of the MAFV capsid protein is approximately two times longer than that of any of the other known flaviviruses. Our results indicate that flaviviruses with distinct features can be found at the edge of the Bolivian Amazon basin at sites that are also home to dense populations of human-biting mosquitoes.